Comparison of muscle activation and kinematics in 6-RM squatting with low and high barbell placement - van den Tillaar, R.; Helms, E. (Journal of Human Kinetics, 2020)
The aim of this study was to compare 6-RM muscle activation and kinematics in back squats with low and high barbell placements. Twelve resistance-trained males (23.5 ± 2.6 years, 86.8 ± 21.3 kg, 1.81 ± 0.08 m) with a minimum of 2 years of squatting experience performed a 6-RM using high and low barbell placements while muscle activation of eight muscles and joint kinematics were measured. During high barbell placement squats, lifting time was longer, with lower average velocity than low barbell placement. This was accompanied by a lesser knee flexion angle at the lowest point of the squat, and larger hip flexion angles during high, compared to low barbell squats. Furthermore, peak angular ankle, knee and hip velocities in the descending phase developed differently between conditions. No significant differences in muscle activation were found between conditions. Thus, our data suggests gross muscular adaptations between barbell placements may be similar over time, and therefore, from a muscular development standpoint, both squat styles are valid. Furthermore, unlike the low barbell placement, fatigue may manifest earlier itself in the high barbell squats during 6-RMs as sets progress toward a lifter`s maximal capacity, altering kinematics, especially in the last repetition.